2022
DOI: 10.1101/2022.02.01.478664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epithelial uptake ofAspergillus fumigatusdrives efficient fungal clearancein vivoand is aberrant in Chronic Obstructive Pulmonary Disease (COPD)

Abstract: Hundreds of spores of the common mould Aspergillus fumigatus (Af) are inhaled daily by human beings, representing a constant, often fatal, threat to our respiratory health. The small size of Af spores suggest that interactions with Airway Epithelial Cells (AECs) are frequent and we and others have previously demonstrated that AECs are able to internalise Af spores. We thus hypothesised that Af spore uptake and killing by AECs is important for driving efficient fungal clearance in vivo and that defective spore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 103 publications
1
24
0
Order By: Relevance
“…Numerous studies have demonstrated that A. fumigatus conidia are readily internalised by AECs in vitro, with both alveolar and bronchial epithelial cells internalising 30–50% of the conidia they encounter [ 17 , 31 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ]. In vitro A. fumigatus uptake by AECs is a time-dependent process, which increases proportionally with longer co-incubations or a higher multiplicity of infections [ 17 , 126 , 128 ]. AECs exert antifungal activity, with intracellular conidia showing impaired germination relative to extracellular conidia [ 17 , 126 ].…”
Section: Are Airway Respiratory Cells Internalising a Fumig...mentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies have demonstrated that A. fumigatus conidia are readily internalised by AECs in vitro, with both alveolar and bronchial epithelial cells internalising 30–50% of the conidia they encounter [ 17 , 31 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ]. In vitro A. fumigatus uptake by AECs is a time-dependent process, which increases proportionally with longer co-incubations or a higher multiplicity of infections [ 17 , 126 , 128 ]. AECs exert antifungal activity, with intracellular conidia showing impaired germination relative to extracellular conidia [ 17 , 126 ].…”
Section: Are Airway Respiratory Cells Internalising a Fumig...mentioning
confidence: 99%
“…In vitro A. fumigatus uptake by AECs is a time-dependent process, which increases proportionally with longer co-incubations or a higher multiplicity of infections [ 17 , 126 , 128 ]. AECs exert antifungal activity, with intracellular conidia showing impaired germination relative to extracellular conidia [ 17 , 126 ]. This antifungal activity has been largely attributed to phagosome acidification [ 122 , 126 ], and, indeed, population- and single-cell studies have demonstrated that the vast majority of internalised conidia (90–97%) are killed by AECs within 12–24 h of infection; however, a small subpopulation is able to avoid clearance and to germinate intracellularly [ 17 , 122 ].…”
Section: Are Airway Respiratory Cells Internalising a Fumig...mentioning
confidence: 99%
See 3 more Smart Citations